TRANSNATIONAL THREATS AND FOREIGN POLICY SHIFTS: INVESTIGATING THE IMPACT OF GLOBALIZATION ON WEST AFRICAN COUNTRIES - AHMED OLAWALE MOLIKI; NURUDEEN ABIDEMI AKANBI (International Studies Journal)
Globalisation is a blessing as well as bane to humanity. Its impact on societies around the globe is diverse, presenting both opportunities and challenges. For most developing countries, the challenges are more than the opportunities. The challenges of terrorism and insurgency in West Africa countries is highly facilitated by the advent of globalisation, and this has greatly impacted how these nations position their foreign policy, shifting from the traditional way of foreign policy making to one that encompasses collaborations to tackle emerging threats. This research therefore explored transnational threats and foreign policy shifts, with a focus on investigating the impact of globalization on West African countries. The paper adopted the use of secondary data collection. Thus, sources of data in the conduct of the study were derived from journals, books, newspaper, institutional publications, and the internet. The paper adopted Complex Interdependence theory as a theoretical framework. The paper observed that West African countries have been significantly affected by globalisation, which has brought them a variety of challenges and opportunities. Therefore, the findings revealed that globalisation, while promoting economic growth, cultural interaction, and technical progress in West Africa states, has also given rise to non-state actors like terrorists and has disruptive consequences for sovereignty and national security. Therefore, the paper concluded that it is necessary for West Africa nations to establish efficient governance systems, regional collaboration platforms, and policies that capitalise on the advantages of globalisation while minimising its negative consequences. The paper recommended that West African countries should prioritize deepening cooperation through regional organizations like ECOWAS, enhancing mechanisms for intelligence-sharing, joint military operations, and capacity-building initiatives to effectively combat transnational threats.